Strategi Kepemimpinan Kepala Sekolah dan Partisipasi Masyarakat dalam Peningkatan Mutu Pendidikan di SDIT Al-Fattah Sukahurip: Principal Leadership Strategy and Community Participation in Improving the Quality of Education at SDIT Al-Fattah Sukahurip - Dahlan, Salma Zaini; Kosasih, Kosasih; Sedarmayanti, Sedarmayanti (Jurnal Pendidikan Sains dan Komputer, 2025)
This study aims to analyze the role of principal leadership in improving the quality of education, explain the contribution of community participation to enhancing the quality of education, and identify factors that influence principal leadership and community participation in these efforts. This study uses a qualitative approach with data collection techniques in the form of in-depth interviews, direct observation, content analysis, and narrative analysis. The primary data sources were obtained from key informants at SDIT Al-Fattah Sukahurip, with a focus on empirical data that reflects the dynamics of the school environment as part of field research. The results of the study indicate that principal leadership has a significant role in improving the quality of education. Principals encourage the professionalism of educators through training, competency development, strategic direction, and motivation. This leadership also reflects the function of the principal as an educator, manager, administrator, supervisor, leader, innovator, and motivator.On the other hand, community participation, especially parents, makes a real contribution through involvement in the school committee, cooperation in education programs, and financial and moral support. Factors that influence the success of principal leadership include dynamic interactions between internal elements of the school and the external environment. Community participation, although significant, is influenced by the level of awareness, socio-economic conditions, and time constraints. This finding emphasizes the importance of synergy between principal leadership and community support to achieve better quality education.